Diabetic foot ulcers: a review of current management - Khan, Yasmee; M. Khan, Manal; Raza Farooqui, M. (International Journal of Research in Medical Sciences, 2017)
Diabetic foot ulcers are a serious complication of diabetes mellitus which increases the patient morbidity and also have significant socioeconomic impact. The present review aims to summarize the causes and pathogenesis leading to diabetic foot ulcers, various classification systems and to focus on the current management of this significant and preventable health condition.